2020
DOI: 10.3390/biom10111564
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Presenilin-Like Transmembrane Aspartyl Protease: Characterization and Cellular Localization

Abstract: The increasing detection of infections of Trypanosoma cruzi, the etiological agent of Chagas disease, in non-endemic regions beyond Latin America has risen to be a major public health issue. With an impact in the millions of people, current treatments rely on antiquated drugs that produce severe side effects and are considered nearly ineffective for the chronic phase. The minimal progress in the development of new drugs highlights the need for advances in basic research on crucial biochemical pathways in T. cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…together with its fractionation to membranes, suggest that the NICT-like protein could also be localized to the endoplasmic reticulum, Golgi complex and mitochondria similar to the T. cruzi presenilin localization [14]. In other cellular systems, the integration of these organelles with PS/γ-secretase complex is responsible for aspects of the secretory pathways [36,37].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…together with its fractionation to membranes, suggest that the NICT-like protein could also be localized to the endoplasmic reticulum, Golgi complex and mitochondria similar to the T. cruzi presenilin localization [14]. In other cellular systems, the integration of these organelles with PS/γ-secretase complex is responsible for aspects of the secretory pathways [36,37].…”
Section: Discussionmentioning
confidence: 82%
“…As epimastigotes are replicative forms, it would be expected that they would have a larger demand for molecules to sustain proliferation. Recently, we have showed that the replicative forms of T. cruzi has the highest levels of PS-like signals, and these results were associated with a potential role for a γ-secretase complex in functions related to proliferation and protein maturation [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To verify the diagnostic performance of the peptides, sera from ninety-two DTP vaccinated individuals were tested on an ELISA-peptide based assay ( Figure 3 A,B). All 92 DTP-positive human sera and 38 mice sera reacted with the highly conserved DTx2–12 and DTx4–13 peptides but did not react with peptide EP7 [ 56 ] from T. cruzi (PPGEDMHTRDGPRE), considered by a scale value as a good test. Both CB/DTx2–12 and CB/DTx4–13 antigens demonstrated 100 and 99.96% sensitivity, respectively, and 100% specificity ( Figure 3 C,D).…”
Section: Resultsmentioning
confidence: 99%
“…While much is known about the GSC compounds in superior eukaryotic organisms, very little is known about their role in inferior eukaryotic cells. Recently, we showed the potential for the presence of a GSC in Trypanosoma cruzi based on our characterization of a TM aspartyl protease that shows hallmarks of human PS [14]. T. cruzi is the causative agent for American trypanosomiasis, more commonly referred to as Chagas disease, and infections are typically spread by triatomine vectors that affect millions of people throughout Latin America [15].…”
Section: Introductionmentioning
confidence: 99%